(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Fingerprint proof is undoubtedly the most solid and adequate proof until date in the official courtroom. Because of the immense capability of fingerprints as a viable strategy for recognizable proof, an endeavor has been made in the present work to examine their relationship with gender and blood group of a person. This planned investigation was completed over a time of 2 months among 200 therapeutic understudies (100 male and 100 female) having a place with the age group 18-25 of Kasturba Medical College, Mangalore, India. Results demonstrate that each finger impression is remarkable loops are the most normally happening fingerprint design while curves are the least normal. Males have a higher rate of whorls and females have a higher occurrence of loops. Loops are predominant in blood group A, B, AB and O in both Rh positive and Rh negative people aside from in O contrary where whorls are increasingly normal. We can infer that there is an association between distribution of fingerprint patterns, blood group and gender and in this manner expectation of gender and blood group of a person is conceivable dependent on his fingerprint design. Fingerprints are ordered and documented dependent on edge patterns. The impressions made by the example of any individual stay unaltered all through life. The investigation was done on 400 people among which 200 were males and 200 were female’s subjects having diverse ABO blood groups, all the 10 fingerprints were isolated into loops, whorl and curves. The outcomes demonstrated that larger part of the subjects had a place with blood group O. The unique mark example of loops had the most astounding frequency while curves were the least. Blood group O were generally connected with the loop design while AB had minimal frequency in all the fingerprint patterns. Males had the most elevated number with the loops and whorls while females had the most astounding number of curves. It was reasoned that there was an association between distribution of fingerprint patterns, blood group and gender and in this way expectation of gender and blood group of a person was conceivable dependent on the fingerprint patterns.